X ray examinations and fractional test meals: an investigation into their usefulness in assisting in the diagnosis of functional and organic disease of the stomach and duodenum - MacCabe, Joseph E. (The University of Edinburgh, 1930)
1. Gastric Ulcer. X Ray is undoubtedly superior to test meals in usefulness. 2. Duodenal Ulcer. Usefulness of X Ray with test meal is about equal. X Ray, of course, gives more accurate information. 3. Carcinoma. Test meal is more useful in diagnosing an early case. 4. Gastritis. The X Ray does not give any help other than in assisting to exclude carcinoma or ulceration, whereas the test meal is very useful, besides aiding the Physician in the diagnosis, it also helps him to exclude carcinoma definitely. 5. Functional Disease. The test meal gives, on the whole, more help to the Practitioner than the X Ray. In cases of functional disease, the X Ray does give a certain amount of help, but it is chiefly in a negative sense, namely, in excluding organic disease, although it does, to a certain extent assist in the diagnosis of hypertonicity and atony. The test meal, on the other hand, is very useful in helping the Physician to diagnose the various conditions of the gastric secretion, besides hypertonicity and atony of the stomach.

I shall finish by stating that if the Physician, or Surgeon, after a careful history and clinical examination has been done, is undecided as to the diagnosis, then a test meal should be performed. If there is still doubt, or if more accurate information is desired, then a radiological examination should be carried out without delay.

Finally, both the results of X Ray examination and the fractional test meal, unless they agree with the history and clinical findings, should be accepted with great caution, or ignored, or else a further examination should be carried out,